Computational Simulation and Modelling of Arterial Drug Delivery From Half-Embedded Drug-Eluting Stents in Single-Layered Homogeneous Vessel Wall - Saha, Ramprosad; Choudhury, Somnath; Mandal, Akash Pradip (Communications in Mathematics and Applications, 2024)
The next-generation of drug therapics has started as a consequence of the invention of controlled-dose pharmaceutical delivery tools. More specifically, coronary angioplasty (CA) treatments often involve drug-eluting stents (DESs) that eluting drug molecules. This mechanism decreases the in-stent restenosis with the help of releasing drugs from a thin polymer membrane covering into the coronary vessel tissue around it. Present day DES equipments, as the protective covering, biodurable polymers has been deployed, that, remains there forever until the drug has fully eluted from DES. In this present work, we investigated the aforementioned problems using a numerical simulation of vascular distribution of drugs as well as receptor binding mechanisms. Modelling is done for the intravascular drug delivery of a hydrophobic (like sirolimus or paclitaxel) drug from DES. The content of this paper discusses the effects of drug delivery from half-embedded circular drug-eluting stent struts. We introduce an elaborate mathematical approach based on axi-symmetry 2D layout, incorporates a two non-linear phases of drug binding namely specific and non-specific, and combines the impact of diffusion and advection, within the single-layered homogeneous vessel wall. The pharmaceutical delivery via five stent struts has been significantly strengthened in this framework. The free pharmaceuticals are moved using an unsteady covection-diffusion- reaction mechanism, even though the binding pharmaceuticals are being through an unsteady reaction-diffusion mechanism. The governing equations along with the initial and boundary conditions has been evaluated numerically using a finite-difference technique in staggered grids. The marker and cell (MAC) methodology has been employed to solved the model equations while taking into account the cylindrical system of polar coordinates. In this present assessment, our target is to visually illustrate the impact of the embedment of the stent on the drug release from stent and vessel drug distribution. According to the findings, it is indicate that the drug gradually binds to specific receptors and extracellular matrix sites until binding sites become saturated. Model simulations have improved our understanding of the potential influences of the different factors that may affect the effectiveness of drug administration. The created modelling allows for the modification of the model’s parameters for upcoming research on the development of PLGA-coated drug-eluting stents.